2013
DOI: 10.3408/jafst.18.45
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Validation of the AmpF^|^#x2113;STR^|^reg; Identifiler^|^reg; Plus PCR Amplification Kit and Comparison of Performance with AmpF^|^#x2113;STR^|^reg; Identifiler^|^reg; PCR Amplification Kit

Abstract: To obtain DNA typing results from forensic biological samples is occasionally di‹cult, since they are complex and diverse. AmpF STRIdentiˆlerPlus PCR Ampliˆcation Kit (IDPlus) was developed to improve the success rate of DNA typing from such samples by Applied Biosystems. Forensic biologists must be cautious in DNA typing when considering the characteristics of the Kit used for analyzing in such samples. Therefore, to reveal to the characteristics of IDPlus Kit is very important to increase the reliability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Earlier cross-species validation studies reported for the non-specific peaks generated from animal DNA are observed in electropherograms near human amelogenin peaks [9][10][11][12]. The shape and observed position of these non-specific peaks are distinct and can be easily distinguished from other artifacts such as dye blobs and primer dimers.…”
Section: A C C E P T E Dmentioning
confidence: 85%
“…Earlier cross-species validation studies reported for the non-specific peaks generated from animal DNA are observed in electropherograms near human amelogenin peaks [9][10][11][12]. The shape and observed position of these non-specific peaks are distinct and can be easily distinguished from other artifacts such as dye blobs and primer dimers.…”
Section: A C C E P T E Dmentioning
confidence: 85%